Analisis Sentimen Ulasan Pengguna E-commerce di Google Play Store Menggunakan Metode IndoBERT - Pradhisa, Kireyna Cindy; Fajriyah, Rohmatul (Forum Kerjasama Pendidikan Tinggi, 2024)
In today's booming digital age, the internet has created global connectivity that links individuals around the world in a global community. Through synergistic collaboration between commerce and information technology, the term e-commerce was born. The analysis of e-commerce product quality is conducted to understand the public's perception of the products offered through the e-commerce platform, which can be accessed through the Google Play Store. The purpose of this research is to find out the sentiment trends of e-commerce users and to know how accurate IndoBERT is in classifying sentiment. By doing so, the founders and managers of both platforms can gain a better understanding of their users' needs and preferences. This information will serve as a foundation for improving service quality and user experience, thereby increasing customer satisfaction and strengthening competitive position in the e-commerce market. In this study, a sentiment analysis of the products of e-commerce platforms Shopee and Bukalapak is conducted, using the NLP-based IndoBERT (Natural Language Processing) model, which classifies the sentiment of user reviews into three categories: negative, neutral, and positive. The review data was taken from Google Play Store with scrapping technique and involved 5000 Shopee and Bukalapak review data with 2500 data each in 2023. The accuracy obtained is 89.84% on Shopee review data and 88.12% on Bukalapak review data. This shows that the model is able to effectively identify sentiment in each user review. Furthermore, another result obtained is that the sentiment of Shopee and Bukalapak e-commerce application users tends to be positive. Therefore, it can be said that the products offered and services carried out by e-commerce platforms Shopee and Bukalapak in 2023 get a good response from the public, which shows that both platforms are trusted and favored by the public.